2013
DOI: 10.1105/tpc.113.115139
|View full text |Cite
|
Sign up to set email alerts
|

ArabidopsisBasic Helix-Loop-Helix Transcription Factors MYC2, MYC3, and MYC4 Regulate Glucosinolate Biosynthesis, Insect Performance, and Feeding Behavior  

Abstract: Arabidopsis thaliana plants fend off insect attack by constitutive and inducible production of toxic metabolites, such as glucosinolates (GSs). A triple mutant lacking MYC2, MYC3, and MYC4, three basic helix-loop-helix transcription factors that are known to additively control jasmonate-related defense responses, was shown to have a highly reduced expression of GS biosynthesis genes. The myc2 myc3 myc4 (myc234) triple mutant was almost completely devoid of GS and was extremely susceptible to the generalist her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
454
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 450 publications
(479 citation statements)
references
References 71 publications
(124 reference statements)
22
454
1
2
Order By: Relevance
“…Consistent with previous studies (Lorenzo et al, 2004;Fernández-Calvo et al, 2011;Schweizer et al, 2013), our results showed that MYC2 upregulated JA-induced expression of the woundresponsive genes VEGETATIVE STORAGE PROTEIN1 (VSP1), VSP2, and TYROSINE AMINOTRANSFERASE3 (TAT3) ( Figure 9A) and the herbivore-inducible genes CYP79B3, BRANCHED-CHAIN AMINOTRANSFERASE4 (BCAT4), and BILE ACID TRANS-PORTER5 (BAT5) (Figure 9B), which are required for the biosynthesis of the secondary metabolites glucosinolates (Zhao et al, 2002;Kliebenstein et al, 2005;Schweizer et al, 2013). Interestingly, the double mutant ein3 eil1 exhibited upregulated expression of these wound-responsive genes (VSP1, VSP2, and TAT3) as well as herbivory-inducible genes (CYP79B3, BCAT4, and BAT5) when treated with (or even without) JA compared with the wild type ( Figures 9A and 9B).…”
Section: Ein3 and Eil1 Attenuate The Transcriptional Activation Functsupporting
confidence: 82%
See 4 more Smart Citations
“…Consistent with previous studies (Lorenzo et al, 2004;Fernández-Calvo et al, 2011;Schweizer et al, 2013), our results showed that MYC2 upregulated JA-induced expression of the woundresponsive genes VEGETATIVE STORAGE PROTEIN1 (VSP1), VSP2, and TYROSINE AMINOTRANSFERASE3 (TAT3) ( Figure 9A) and the herbivore-inducible genes CYP79B3, BRANCHED-CHAIN AMINOTRANSFERASE4 (BCAT4), and BILE ACID TRANS-PORTER5 (BAT5) (Figure 9B), which are required for the biosynthesis of the secondary metabolites glucosinolates (Zhao et al, 2002;Kliebenstein et al, 2005;Schweizer et al, 2013). Interestingly, the double mutant ein3 eil1 exhibited upregulated expression of these wound-responsive genes (VSP1, VSP2, and TAT3) as well as herbivory-inducible genes (CYP79B3, BCAT4, and BAT5) when treated with (or even without) JA compared with the wild type ( Figures 9A and 9B).…”
Section: Ein3 and Eil1 Attenuate The Transcriptional Activation Functsupporting
confidence: 82%
“…MYC2 functions as a key transcription factor to positively regulate diverse JA responses (Kazan and Manners, 2013), including root growth (Boter et al, 2004;Lorenzo et al, 2004), secondary metabolism (Dombrecht et al, 2007;Hong et al, 2012;Schweizer et al, 2013), wound response, and plant defense against insect attack (Zhang and Turner, 2008;Fernández-Calvo et al, 2011;Schweizer et al, 2013). Surprisingly, MYC2 also acts as a negative regulator to repress JA-mediated plant resistance to necrotrophic fungi and pathogenesis-related gene expression (e.g., PDF1.2) (Anderson et al, 2004;Lorenzo et al, 2004;Zhai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations